An Economic Perspective on Policies to Save the Vaquita: Conservation Actions, Wildlife Trafficking, and the Structure of Incentives - Sanjurjo-Rivera, Enrique; Mesnick, Sarah L.; Ávila-Forcada, Sara; Poindexter, Oriana; Lent, Rebecca; Felbab-Brown, Vanda; Cisneros-Montemayor, Andrés M.; Squires, Dale; Sumaila, U. Rashid; Munro, Gordon; Ortiz-Rodriguez, Rafael; Rodriguez, Ramses; et al. (Frontiers in Marine Science, 2021)
The Upper Gulf of California is a diverse and highly productive ecosystem supporting some of the most important fisheries in Mexico, yet a history of weak fishery management and illegal fishing threatens the area’s biodiversity and undermines human well-being in the communities along its shores. The vaquita (Phocoena sinus) is endemic to these waters and is on the brink of extinction due to incidental entanglement in gillnets used by small-scale fishers. The resurgence of an illegal gillnet fishery for totoaba (Totoaba macdonaldi), whose swim bladders are highly prized in Hong Kong and continental China has exacerbated the decline of vaquita. Vaquita is one of a growing number of cases linking illegal wildlife trade, organized crime, and biodiversity decline. This paper provides a summary of key reflections of a panel of fisheries economists gathered at the ninth forum of the North American Association of Fisheries Economists (NAAFE) to evaluate the policies implemented in the Upper Gulf through an economic lens and updated to reflect more recent developments. The panel found that poor fisheries management, lack of effective enforcement, distant demand for an illegal product, corruption, and few viable economic alternatives were key challenges in addressing vaquita bycatch. The complexity of these problems requires a holistic, multidisciplinary approach, combining top-down (direct regulation) and bottom-up, participatory and incentive-based approaches, to improve governance and enhance community participation and therefore strengthen compliance. Enforcement is a key component of ensuring top-down policies are implemented, and equally crucial, actions to support legal fishermen able to make a good living—with a stake or ownership of their own resources—are important components of policies to address bycatch and also to reduce wildlife trafficking. The Upper Gulf situation is dire, yet similar threats to other marine mammals and wildlife trafficked species may benefit from the experience of the vaquita.